An evaluation study of the determinants of future perspective and global Quality of Life in Spanish long-term premenopausal early-stage breast cancer survivors - Arraras, Juan Ignacio; Illarramendi, Jose Juan; Salgado, Esteban; Cruz, Susana de la; Asin, Gemma; Manterola, Ana; Ibañez, Berta; Zarandona, Uxue; Dominguez, Miguel Angel; Vera, Ruth (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Quality of life (QL) is important in premenopausal long-term breast cancer survivors. In this study we assessed QL and factors associated with future perspective and global QL in premenopausal early-stage long-term breast cancer survivors from Spain. Material and methods : 243 premenopausal stage I-IIIA relapse-free breast cancer patients who had received surgery 5–20 years previously completed EORTC QLQ-C30 and QLQ-BR23 questionnaires once during follow-up. Univariate and multivariate logistic regression analyses were performed. Results : QL mean scores were high in most areas (> 80 in functioning; < 20 in symptoms). The main factors for future perspective were emotional and social functioning, fatigue, breast symptom, and body image. The main factors for global QL were fatigue, pain and physical functioning, and emotional and social functioning. The best logistic model to explain future perspective associated high emotional and social functioning and low breast symptoms with a lower risk of low future perspective (R 2 = 0.56). Higher scores in physical and emotional functioning and lower scores in fatigue were associated with a lower risk of low global QL (R 2 = 0.50). Conclusions : Psychological, social, and physical factors were found to be possible determinants of global QL and future perspective. QL in premenopausal early-stage long-term breast cancer survivors may benefit from multidisciplinary treatment.